First record of Phoenicococcus marlatti in Greece - Lytra, I. Ch.; Vasarmidaki, M. E.; Papadoulis, G. Th. (ENTOMOLOGIA HELLENICA, 2013)
In October 2013, the red date scale Phoenicococcus marlatti Cockerell (Hemiptera: Phoenicococcidae) has been recorded for the first time in Greece. Adult females were collected from the base of fronds of date palm from the Crete Island. Information on the species morphology, biology and distribution is presented.